2020
DOI: 10.1007/978-3-030-50029-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Weighted PCL over Product Valuation Monoids

Abstract: We introduce a weighted propositional configuration logic over a product valuation monoid. Our logic is intended to serve as a specification language for software architectures with quantitative features such as the average of all interactions' costs of the architecture and the maximum cost among all costs occurring most frequently within a specific number of components in an architecture. We provide formulas of our logic which describe well-known architectures equipped with quantitative characteristics. Moreo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Hence, it would be interesting to investigate whether we could relax the idempotency property of the semiring K. Another work direction includes studying the concept of weighted connectors over more general structures than semirings, that are currently used in practical applications, for instance valuation monoids (cf. [DM11,KP20]). Another problem is developing a theory for modeling not only connectors but also the underlying behavior of component-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it would be interesting to investigate whether we could relax the idempotency property of the semiring K. Another work direction includes studying the concept of weighted connectors over more general structures than semirings, that are currently used in practical applications, for instance valuation monoids (cf. [DM11,KP20]). Another problem is developing a theory for modeling not only connectors but also the underlying behavior of component-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would be interesting to extend our logic-based framework for the investigation of dynamic and reconfigurable architectures [BJMS12, CST18, MG16] as well as for addressing the architecture composition problem [ABB + 16, BHM19]. Another research direction is the study of our logics over alternative weight structures, found in applications, like for instance valuation monoids [DM11,KP20]. Formal approaches for architectures are often extended with tools or graphical languages for supporting architectures' specification (cf.…”
Section: Modelling Of Parametric Architectures 26:31mentioning
confidence: 99%
“…Finally, according to our best knowledge the only weighted logic-based approach for the modelling of architectures is found in the recent work of [KP20,PR17,PR20a]. Specifically, in [PR17,PR20a] the authors studied PCL in the weighted setup for modelling the quantitative aspects of architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation